RELASI PERTUKARAN SOSIAL:: PETANI BAWANG MERAH DAN TENGKULAK DI NGANJUK JAWA TIMUR - Clara Hosana Yessica Jelita Dewi; Arnelita Natalie Antonio; Clarissa Serena Wibowo; Inggrid Devyana Chandra; Jennifer Olivia Lapod; Valencia Lo (Universitas Ciputra Surabaya, 2023)
Abstract. Enormous contribution of the agricultural sector does not necessarily improve the welfare level among farmers. Previous research shows that farmers are dependent on middlemen, therefore they tend to give in and agree with the price decided by middlemen. However, there are different conditions in Nganjuk. The purpose of this research is to identify actors involved, strengths and power, as well as social exchange between shallot farmers who have bargaining power and middlemen in Nganjuk regency, East Java. This study uses a qualitative approach with thematic analysis, utilizing interview and photo documents as a form of collecting the data. Participants involved in this study were 2 farmers, 3 middlemen, and village headman. Result shows that farmers’ bargaining power is shown by ownership of resources, alternative sales, and ability to negotiate prices. Other than shallots and money being the main material exchange resources, trust as part of the process is a non-material exchange resource. This study found that driving factors between farmer-middleman exchange relations were trust, a sense of kinship, profit, and professionalism between actors involved. Whereas risk factors involve breach of agreement. Another interesting finding is the existence of a key actor, namely the village head as a mediating figure. Limitations in this research include language barriers, lack of in-depth probing due to the farmers and middlemen having double jobs, and limited access to brokers as the relation medium.